Case for change: a standardised inpatient paediatric early warning system in England. Issue 7 (8th January 2021) - Roland, Damian; Stilwell, Philippa Anna; Fortune, Peter-Marc; Alexander, John; Clark, Simon J; Kenny, Simon
Abstract : Most children in hospital who are clinically deteriorating are monitored regularly, and their treatment is escalated effectively. However a small, but significant, number of deteriorating children experience suboptimal outcomes because of a failure to recognise and respond to acute deterioration early enough leading to unintended harm. Tragically this occasionally can have fatal consequences. Investigations into these rare events highlight common themes of missed early signs of deterioration in children, prompting regulatory agencies to suggest paediatric early warning systems (PEWS) to aid clinical practice. In England, track and trigger tools (TTT), which are one facet of PEWS have been widely rolled out but in a heterogeneous fashion. The evidence for TTT is mixed but they are complex interventions and current outcomes do not fully define the entirety of their potential impact. This article explains the rationale behind the decision of the NHS England and NHS Improvement, Royal College of Paediatrics and Child Health and Royal College of Nursing to implement a standardised inpatient PEWS as part of a system-wide paediatric observations tracking system in England and how this fits into a wider programme of activity.